The Effect of A PowerPoint-based Collaborative Learning Model on Student Learning Outcomes on the Theme of Togetherness in Class II Agia Shopia Private Primary School - Hesli Yohana br Manullang, Mona; Janson Silaban, Patri; Sofia Tanjung, Darinda; Lumban Gaol, Rumiris; Wulansari HS, Dyan (Jurnal PAJAR (Pendidikan dan Pengajaran), 2024)
The present study aims to determine the effect of the PowerPoint-based collaborative learning model on student learning outcomes on the theme of togetherness in class II of Agia Sophia Private Elementary School. This research is quantitative research. The research subjects were class II students at Agia Sophia Private Elementary School. The research instrument is a questionnaire with multiple choice test instrument. Student learning outcomes using collaborative learning model obtained an average score of 79.8. Meanwhile, learning outcomes without using the collaborative learning model were 66.3 and for the questionnaire, the students obtained an average score of 85.7. Furthermore, the hypothesis result shows that tcount is 7.212 while ttable is 2.042. It proves that the hypothesis is greater, so Ho is rejected and Ha is accepted. This indicates that there is an effect between collaborative learning model learning and student learning outcomes.